Secular trends in semen parameters among men attending a fertility center between 2000 and 2017: Identifying potential predictors. (December 2018) - Mínguez-Alarcón, Lidia; Williams, Paige L.; Chiu, Yu-Han; Gaskins, Audrey J.; Nassan, Feiby L.; Dadd, Ramace; Petrozza, John; Hauser, Russ; Chavarro, Jorge E.; ,
Abstract: Background: Multiple meta-analyses have shown sperm count declines in Western countries spanning eight decades. Secular trends in other parameters remain unclear, as are potential predictors of these trends. Objective: To analyze secular trends in semen quality and to evaluate whether factors previously found to be related to semen quality were responsible for these patterns. Methods: This is a prospective study including 936 men of couples seeking infertility treatment who provided 1618 semen samples at a single center (2000–2017). Self-reported demographic, nutritional and reproductive characteristics were collected using standardized questionnaires. Urinary concentrations of bisphenol A, parabens and phthalates were quantified by isotope-dilution tandem mass spectrometry. Semen samples were analyzed for volume, sperm concentration, count, motility and morphology following WHO guidelines. We estimated the differences in semen parameters over time by fitting generalized linear mixed models with random intercepts to account for repeated samples while adjusting for abstinence time. We also adjusted for demographic, nutritional and environmental factors to investigate these as potential predictors of time trends. Results: Sperm concentration and count declined by 2.62% per year (95% CI −3.84, −1.38) and 3.12% per year (95% CI: −4.42, −1.80), corresponding to an overall decline of 37% and 42%, respectively, between 2000 and 2017. Decreasing trends were also observed for total motility (per year: −0.44 percentage units, 95% CI −0.71, −0.17) and morphologically normal sperm (per year: −0.069 percentage units, 95% CI −0.116, −0.023). These decreases reflected relative percentage declines of 15% and 16% over the 17 year study period, respectively. When reproductive factors were included in the model, the downward trends in sperm concentration and sperm count were attenuated by 29% and 26%, respectively, while the trends in motility and morphology were attenuated by 54% and 53%, respectively. Also, the downward trends in both sperm concentration and sperm morphology over time were attenuated by 19% when including the DEHP and non-DEHP metabolites, respectively. Conclusions: Sperm concentration, total count, motility and morphology significantly declined between 2000 and 2017 among subfertile men. These negative trends were attenuated when considering simultaneous changes in reproductive characteristics and urinary phthalates during the course of the study. Highlights: Sperm concentration and count declined 37% and 42%, respectively, between 2000 and 2017 among men attending a fertility center in Boston. Total motility and morphologically normal sperm declined 15% and 16% over the 17 year study period, respectively. When reproductive factors were included in the model, the downward trends in semen parameters were attenuated between 29% and 54%. The downward trends in sperm concentration and morphology were attenuated by 19% when including the DEHP and non-DEHP metabolites, respectively.